Analisis Kebijakan Penanggulangan Kemiskinan di Indonesia: Kajian terhadap Program Keluarga Harapan (PKH) Tahun 2019–2023 - Arniati Lamusu; Anatasya Putri; Ariyansyah S Hunowu; Hartati Talib; Nurmila Lakoro (JURNAL ILMIAH NUSANTARA, 2026)
Poverty remains one of the most deeply rooted socioeconomic challenges in Indonesia. As a strategic policy response, the Hopeful Families Program (PKH) has been implemented since 2007 with the aim of reducing poverty and improving the human capital of the poorest households. This study analyzes the effectiveness of PKH as a conditional cash transfer program in Indonesia from 2019 to 2023, focusing on its implementation mechanisms, accuracy of beneficiary selection, and measurable outcomes related to poverty reduction. Using a qualitative descriptive approach with document analysis and secondary data review, this study examines government reports, national statistics, and peer-reviewed literature. Findings show that PKH contributed significantly to reducing the poverty rate, which fell from 9.22% in 2019 to 9.36% in 2020 due to the impact of the COVID-19 pandemic, then recovered to 9.54% and gradually fell to 9.03% by 2023. During the pandemic, PKH payments were increased to cushion economic shocks, demonstrating the adaptability of the program. However, challenges remain, including inaccuracies in beneficiary data selection, low graduation rates among beneficiaries, regional differences in program implementation, and insufficient integration with complementary social security programs. This study recommends strengthening integrated social data systems, improving local government capacity, and designing clearer graduation pathways to promote long-term socioeconomic independence of PKH beneficiaries. Policy reforms that address these structural constraints are critical to optimizing the role of PKH in achieving Indonesia's national poverty reduction goals.